Infant behaviour questionnaire - revised version: a psychometric study in a Portuguese sample - Costa, Raquel (2018)
Background: Although the original characteristics of temperament tend to remain constant over the course of development, environmental circumstances may influence infants’ reactions and behaviour. Parents’ reports of infant temperament are rich informants of infant behaviours in different contexts. Objective: This study aimed to examine the psychometric properties of the Portuguese version of the Infant Behaviour Questionnaire – Revised (IBQ-R) and test the adequacy of the original and other previously published structures to the Portuguese data. Method: 330 mothers and 81 fathers of children aged between 3 and 12 months completed the Portuguese version of the IBQ-R. Results: The confirmatory factorial analysis revealed a non-adequate model fit of the IBQ-R original structure to the Portuguese data; nonetheless, it did reveal an adequate model fit of a previous published IBQ-R structure. This structure, although only slightly different from the original one, seems to be more suitable for the Portuguese data. Conclusion: This study provides data that indicates that the IBQ-R is a reliable questionnaire to evaluate infant temperament in the Portuguese culture.